THE RELATIONSHIP OF SLEEP QUANTITY AND QUALITY WITH DEMENTIA IN TANKER SHIP SAILERS - Rebeca Abislong, Belatrix; Paskarini, Indriati (HEARTY, 2025)
Introduction : Sleep is an important aspect that plays a role in health and thinking processes. Seafaring is a job with a high level of mobilization and uncertain working hours causing less sleep time and having fatal consequences for health as such dementia. As less as reduction in 1% of deep sleep per year for people whohad ages over 60 years reflected as 27% improving the risk of dementia. Aims : This study aimed to help determining the influence of the quantity and quality of sleep and the level of dementia in tanker sailors PT. X Jakarta. Method : This research is a mixed qualitative and quantitative research with a cross-sectional approach with a total of 43 respondents selected by using random sampling techniques. The dependent variable used is the sailor’s dementia level and the independent one is the sailor’s sleep quality. It was found that 30 respondents had poor sleep quality, Based on the MMSE questionnaire’s results, there are 15 respondents had moderate levels of dementia and 5 respondents had severe levels of dementia. Result : The results of statistical tests using Pearson with SPSS software obtained a Sig value. (2-tailed) between the sleep quality variable and dementia is 0.000 < 0.05, so it is meant that there is a significant correlation of sleep quality toward dementia. Conclusion : This study concluded that there was a correlation of sleep quality and dementia in PT. X Jakarta.